2010
DOI: 10.1074/jbc.m109.060061
|View full text |Cite
|
Sign up to set email alerts
|

AMP-activated Protein Kinase Signaling Activation by Resveratrol Modulates Amyloid-β Peptide Metabolism

Abstract: Alzheimer disease is an age-related neurodegenerative disorder characterized by amyloid-␤ (A␤) peptide deposition into cerebral amyloid plaques. The natural polyphenol resveratrol promotes anti-aging pathways via the activation of several metabolic sensors, including the AMP-activated protein kinase (AMPK). Resveratrol also lowers A␤ levels in cell lines; however, the underlying mechanism responsible for this effect is largely unknown. Moreover, the bioavailability of resveratrol in the brain remains uncertain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
445
2
5

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 583 publications
(482 citation statements)
references
References 72 publications
(85 reference statements)
23
445
2
5
Order By: Relevance
“…As reported for young and middle-aged mice (Grossi et al, 2013), an astonishing activation of the autophagic lysosome system was observed also in 12-month-old Tg mice and, to a lesser extent, in age-matched wt controls. These data agree with a similar behavior displayed also by other natural phenols (Li et al, 2011;Vingtdeux et al, 2010) and, in our case, suggest that this pathway is involved in the removal of toxic Aß aggregates also in the advanced stage of the disease.…”
Section: Discussionsupporting
confidence: 93%
“…As reported for young and middle-aged mice (Grossi et al, 2013), an astonishing activation of the autophagic lysosome system was observed also in 12-month-old Tg mice and, to a lesser extent, in age-matched wt controls. These data agree with a similar behavior displayed also by other natural phenols (Li et al, 2011;Vingtdeux et al, 2010) and, in our case, suggest that this pathway is involved in the removal of toxic Aß aggregates also in the advanced stage of the disease.…”
Section: Discussionsupporting
confidence: 93%
“…A current Phase II clinical trial that combines curcumin and yoga therapy aims to treat MCI (ClinicalTrials.gov identifier: NCT01811381). Resveratrol found in red grape skin is a potent antioxidant that has been shown to reduce amyloid plaque burden and improve memory deficits in transgenic AD mouse models [132,133]. Resveratrol activates the 5'adenosine monophosphate-activated protein kinase pathway, and stimulates activity of nicotinamide adenine dinucleotide-dependent deacetylase sirtuin-1 [134,135], which subsequently activates the PGC1α metabolic regulatory pathway and promotes mitochondrial biogenesis [136][137][138][139].…”
Section: Oxidative Damage As a Therapeutic Targetmentioning
confidence: 99%
“…Latrepirdine is proposed to interact with glutamate Reduces oxidative stress, reduces amyloid plaques, improves memory deficits in transgenic mouse models of AD No major effect on cognitive function [132][133][134][135][136][137][138][139] AD = Alzheimer's disease; ROS = reactive oxygen species; SOD = superoxide dismutase; MitoQ = mitoquinone mesylate; AMPK = adenosine monophosphate-activated protein kinase; NAD = nicotinamide adenine dinucleotide; SIRT1 = sirtuin 1 receptors, block voltage-dependent calcium channels, and inhibit mitochondrial permeability, thereby suppressing unnecessary mitophagy or apoptosis [153,154]. In a Phase II clinical trial in patients with moderate AD, it significantly improved cognitive function over placebo [155].…”
Section: Apoptosis and Mitophagy As Therapeutic Targetsmentioning
confidence: 99%
“…Experiments on AD transgenic mouse models with oral resveratrol administration showed that A levels and deposition were reduced in the cortex compared to controls [29]. Resveratrol pronouncedly decreased the amounts of secreted and intracellular A peptides generated from different cell lines by facilitating intracellular degradation of Aβ involving the proteasome [63].…”
Section: Discussionmentioning
confidence: 99%
“…Resveratrol has been found to activate AMPK in neuroblastoma cells and primary neurons in vitro as well as in the brain by activating calcium/CaMKKβ/AMPK signaling pathways [28,29].…”
Section: Introductionmentioning
confidence: 99%